Ethical Problems in Communication and Law At The Creation of the Survey’s Ethics Board - Nanang Trenggono (Universitas Lampung, 2020)
Public reports of misconduct survey institution in the local leader election arrangement, put the Komisi Pemilihan Umum Provinsi (KPU) provinsi or the Province’s General Election Commission has an optional authority, can form an ethics council or submit to the survey association. Then it became a matter, because of the verdict is “a half truth,” potentially damaging ego or the pride of another. Ethics council establishment as the enforcement of institutional authority should begin with clarification as a consequence of ethics in communication, and it requires technical guidance from The National Election Commission to fulfill the ethical weight of the law. But there is a conflict of interest when issues are refered to the survey association. When on trial, on the Dewan Kehormatan Penyelenggara Pemilu (DKPP) or the Honorary Election Board, the decision is evident contradictions; in consideration of appreciation, amar sanctioned the warning.